Scientific Concept According to Islamic Perspective - Salamiyah, Salamiyah (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2020)
The scientific approach is the learning process with the activities of observing, asking, processing, presenting, concluding and creating. In Islamic there has been explained an explanation of the process of learning. Regarding this includes the process of working memory, mastery of knowledge and skills. This research uses the literature method and the data are analyzed descriptively. The scientific concept in Islamic has been carried out by prophets and apostles and has been developing until now. We can take a scientific approach from the story of Adam about knowing the names (Asma) and Abraham in seeking God. In both stories there is a scientific concept process that is (1) observing, (2) asking, (3) gathering information, (5) associating, and (6) communicating.